Fabrication of Palm Leaf Fiber Board Biocomposite for Thermal Insulation Material - Kusmawati, Intan; Yana, Debi; Husna, Ropiqotul; Aisah, Nurul; Syahputra, Romi Fadli; Ginting, Delovita (Lambung Mangkurat University Press, 2024)
Utilizing palm frond biomass for the production of composite materials will have a positive impact on managing palm oil plantation waste. Palm frond fiber biocomposite products have been proven to have good mechanical properties. However, exploration of other physical properties, especially thermal insulation properties, has not been widely studied. As a non-conducting material, palm frond fiber has the potential to have good thermal insulation properties. This study aims to fabricate palm frond biocomposite fiberboard, which has potential as a thermal biocomposite material. Fiberboard is made using the manual hand lay-up technique and cold compaction using a press machine. The characteristics under consideration for the fiberboard in concern encompass its physical, mechanical, and thermal properties. The main ingredients utilized in the fabrication of fiberboard predominantly comprise palm frond fiber and epoxy resin, with five distinct sample variants denoted as PSP-1 (84% fiber:16% resin), PSP-2 (83% fiber:17% resin), PSP-3 (82% fiber:18% resin), PSP-4 (81% fiber:19% resin), and PSP-5 (80% fiber:20% resin). The experimental results obtained from the testing of physical parameters indicated that the density of fiberboard exhibited a range of values spanning from 0.28 g/cm3 to 0.55 g/cm3. Similarly, the fiberboard's water absorption capacity varied between 107.25% and 194.00%. The water absorption abilities display significant variability, as indicated by a large standard deviation ranging from 28.15% to 80.35%. When the density of fiberboard is high, its water absorption capacity tends to be low. Furthermore, the mechanical tests revealed that the fiberboard's flexural strength showed a range of values spanning 1.10-5.42 MPa. The magnitude of specific heat capacity for fiberboard is calculated to be between 2.1-3.5 J/g ̊C, while the thermal conductivity lies within the range of 0.001-0.0020 W/mK